Housing Policies in China: Issues and Options - Yves Zenou (Research Institute of Industrial Economics (IFN), 2010)
This article consists in three parts. The first part deals with theory. We evaluate the pros and cons of government involvement in urban housing and of renting versus ownership. In the second part, we summarize the different housing policies that have been implemented in the United States, Europe, and Asia. We draw some conclusions. In particular, we show that there is a tradeoff between encouraging home ownership and social housing since countries that have favor the former have neglected the latter (like Japan, Spain, etc.). In the third part, we use the theory and the international policy parts to address housing policy issues in China. One of the main concerns in Chinese cities is the raise of poverty mainly by illegal migrants (who are Chinese rural residents) living in urban villages. We propose two steps to fight against poverty in Chinese cities. The first one is to require that the Chinese government recognizes these illegal migrants by helping them becoming legal. The second step is to encourage social housing that directly or indirectly subsidizes housing for the poor. In that case, to fight against poverty, one can either implement place-targeted policies (like the enterprise zone programs in the US and Europe and/or housing projects in the US, UK, or France) or people-targeted policies (like the MTO programs in the US). We also discuss other issues related to poverty. In particular, we suggest that the government could also try to keep migrants in rural areas by attracting firms there and/or introduce a microfinance system that helps them become entrepreneur.
Keywords: H50; O53; 330; Urban villages; Social housing; Poverty; Place-targeted policies; People-targeted policies; China; Wohnungspolitik; Soziale Wohnungspolitik; Armutspolitik; Städtische Armut; Binnenwanderung; Stadt; China